LOCL-04 SAFETY AND FEASIBILITY OF RHENIUM-186 NANOLIPOSOME (186RNL) IN LEPTOMENINGEAL METASTASES [LM] PHASE 1/2A DOSE ESCALATION TRIAL. (5th August 2022) - Brenner, Andrew; Youssef, Michael; LaFrance, Norman; Hedrick, Marc; Bao, Ande; Phillips, William; Patel, Torel; Weinberg, Jeffrey; Floyd, John
Abstract: BACKGROUND: LM is a devastating subarachnoid (SA) complication most commonly from breast, lung, melanoma, and gastrointestinal malignancies affecting 110, 000 in the USA. Common therapies are radiation and SA/IV chemotherapy. Without treatment, survival is short with limited treatment options and better options urgently needed. 186RNL emits beta particles (with gamma-rays) with low dose rate and high radiation density. We report first results of the enrolling ReSPECT-LM phase 1/2a 186RNL-LM dose escalation trial. MATERIAL AND METHODS: Preclinical syngeneic rat model animals were 186RNLtreated at day15 with intraventricular186RNL(0.689 mCi) providing mean CSF-radiation absorbed dose=1, 136 ±226Gy. 50% control animals[unloaded liposomes] and 100%186RNL treated animals were alive at 14days. At 4 weeks, 75% control animals and 37.5% treated animals had died. Based on this preclinical data and 186RNL recurrent glioma human experience, a phase I/2a dose escalation ReSPECT-LM Trial was initiated to characterize safety/tolerability of a single intrathecal(IT) 186RNL administration. Following, to identify maximum tolerated/feasible doses, 186RNL anti-tumor activity as a single agent in LM patients (breast and NSCLC), characterize 186RNL pK & dosimetry via Ommaya delivery, determine the overall response rate (ORR) for 186RNL treated patients based on CSF/radiographic findings, and describe survival distribution. RESULTS: ReSPECT-LM is enrolling and 1st patient dosed (6.6 mCi186RNL, 5ml) via Ommaya reservoir. The dose was well-tolerated with no complaints/AEs as of Day 28 following treatment. Imaging and CSF tumor cell assays at pre &post-dose were performed. 186RNL gamma imaging confirmed rapid, complete and durable SA dose distribution through168hours. Pre-dose CSF tumor cell count was 70.77 cells/ml and following treatment, 39.79 cells/ml at 24, and ~6 cells/ml at both 48 &168hours. CONCLUSION: 186RNL's unique formulation and characteristics may have promise for LM patients. An update of the ReSPECT-LM clinical trial will be provided.